PENYELENGGARAAN PEMBANGUNAN INFRASTRUKTUR DESA DI DESA NUSANTARA JAYA KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR TAHUN 2015 - Rahman, Novy; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
The village administration is spearheading national development which is led by a village chief as the holder helm of the highest in the country, as the main determinant for success in rural development. As supreme leader, village head should perform well in the governance process stipulated in Law No. 6 2014. Implementation of Rural Infrastructure Development is the development of village infrastructure such as public facilities and infrastructure. Implementation of village infrastructure development such as public facilities and infrastructure aims to improve the welfare of people and improve human resources, expected in order to improve a better life, which is implemented through a pattern of community empowerment. However, irregularities in implementation of rural infrastructure development, this was due to lack of supervision in the implementation of rural infrastructure development. The purpose of this study is to identify and analyze the implementation of infrastructure development in the village of Desa Nusantara Jaya subdistrict Keritang Indragiri Hilir. The concept of the theory used is the management which includes planning, organizing, implementation and supervision. To analyze the implementation of rural infrastructure development in the Village Nusantara Jaya subdistrict Keritang Indragiri Hilir, researchers used the theory of George R.Terry in Manullang (2012: 8), this study uses qualitative research methods to study descriptively. In collecting the data, the authors use the technique of interview, observation and documentation. By using key informen as a source of information and as a source triangulation techniques in testing the validity of the data. The results of this study indicate that the implementation of rural infrastructure development are not fully implemented in accordance with existing regulations. In the implementation of rural infrastructure development is still the occurrence of irregularities in the process of development of rural infrastructure. Meanwhile inhibiting factors in the implementation of rural infrastructure development is the budget or the perceived costs less. Inaccuracy of materials, time and labor in the implementation of rural development. KeyWords: Implementation, Development, Rural Infrastructure